The Aquifer System Within the Crystalline Rocks of the Jos - Plateau and Environs (Journal of Pure and Applied Sciences (Science Forum), 2025)
An investigation into the aquifer system of the crystalline rocks within Jos andenvironments was carried out. The area covered some selected sites from thenorthern senatorial zone down to southern senatorial zone of the state. Thegeology of each site was study to establish the grain size, texture and geologicalstructures associated with each of the rock type. The rock types in the area are:migmatites, gneisess, granites, and basalts. Vertical electrical sounding (VES)using the Schlumberger full electrode spread was adopted for the geophysicalinvestigation. The spread ranged from 95m-215m. the software IX1D Packagedeveloped by Interpex Limited was used for plotting data and iteration of thecurves. Thereafter drilling of favourable sites were carried out as the clients couldafford at that time using PAT DRILL 301, 401, and Indian Motor Rigs. The VEScurves showed that the basement rocks are characterized by A, KHA and KHKcurves types. Most of the VES points have four geoelectric layers whose apparentresistivities range from 19Ω -344Ω. The younger granites are characterized by Hand HA curves of which the H curves dominate. Here, the geoelectric layer and theapparent reistitvies range from 4-5 and 21 Ω -834Ω respectively. Within thebasement complex, drilling revealed that the aquifers are located mainly withinthe basement rocks, while within the younger granites, they are located at thecontact between the regolith and the crystalline rocks and also within thecrystalline rocks as fractures. In terms of drillabiblity, the aquifers within thecrystalline rocks have low drillability than the unfractured or fresh rocks. Whereaswithin the regolith, the aquifers have high drillability than the non aquiferious clay.Drilling also showed that coarse grain rocks are more aquiferious than fine grainrocks when weathered. From the investigations, the chances of gettinggroundwater is higher within the basement complex than the younger granites asthe basement complex are more deformed and altered.